PENGARUH PENGETAHUAN PENGELOLAAN INFORMASI DAN ETOS KERJA TERHADAP DAYA SAING GURU DI SMA NEGERI SE-KOTA DENPASAR - Rahma Regina (Universitas Negeri Jakarta, 2012)
The objective of this casual research is to obtain informating concerning the influence of information management knowledge and work ethic to teacher competitiveness. The research was conducted by using a survey method with path analysis in testing hypothesis. In this research, 233 samples of teachers were selected in random. The research was focused on three aspect; information management knowledge, work ethic and competitiveness. The result of the research as follow: (1) There is a direct positive effect of information management knowledge on teacher competitiveness in state Senior High School Denpasar, (2) there is a direct positive effect of work ethic on teacher competitiveness in state Senior High School Denpasar, (3) there is a direct positive effect of information management knowledge on teacher competitiveness in state Senior High School Denpasar. Therefore, teachers competitiveness can be improved by gaining the information and elevate the personnel’s work ethic by way of training, and workshops.